Platelet glycoproteins and fibrinogen in recovery from idiopathic sudden hearing loss. - Daniel Weiss; Bruno Neuner; Kerstin Gorzelniak; Alexis Bremer; Claudia Rudack; Michael Walter (PLoS ONE, 2014)
BACKGROUND: The pathomechanism and location of idiopathic sudden sensorineural hearing loss (ISSHL) is unclear. In a previous case-control study, we found elevated fibrinogen concentrations and a higher prevalence of T allele carriers of the glycoprotein (Gp) Ia C807T polymorphism in ISSHL patients. METHODOLOGY: 127 patients with ISSHL (mean age 53.3 years, 48.8% females), who underwent a standard therapy with high dose steroids, pentoxifyllin and sterofundine over 8 days were included. We examined the influence of GpIa genotype and fibrinogen (BclI-, A312-, HaeIII-) genotype and fibrinogen plasma levels on hearing recovery after 8 weeks (change from baseline: 0 dB  =  no recovery, >0 to 10 dB = moderate recovery, >10 dB = good recovery). In a subsample of 59 patients with ISSHL, we further studied the association of platelet glycoprotein GpIa, Ib and IIIa densities on hearing recovery as well as the possible effect-modification of platelet glycoproteins on hearing recovery by plasma fibrinogen. RESULTS: In univariate analysis, neither the GpIa genotype nor fibrinogen genotype (all p>0.1) but lower fibrinogen levels (p = 0.029), less vertigo (p = 0.002) and lower GpIIIa receptor density (p = 0.037, n = 59) were associated with hearing recovery. In multivariate analysis, fibrinogen significantly modified the effect of GPIa receptor density on good hearing recovery (effect-modification on multiplicative scale OR = 0.45 (95% confidence interval (0.21-0.94)), p = 0.03). GPIb receptor density below the mean was associated with a 2-fold increase in good hearing recovery both in patients with fibrinogen levels above (p = 0.04) as well as in patients with fibrinogen levels below the mean (p = 0.06). There was no indication for an effect-modification (p = 0.97). CONCLUSIONS: The findings suggest a vascular/rheological origin of ISSHL with unique features of thrombosis in the inner ear artery that may include complex interrelationships among platelet glycoproteins and plasma fibrinogen.